Brain and Retinal Abnormalities in the 5xFAD Mouse Model of Alzheimer's Disease at Early Stages - Zhang, Mengrong; Zhong, Liting; Han, Xiu; Xiong, Guoyin; Xu, Di; Zhang, Sensen; Cheng, Haiyang; Chiu, Kin; Xu, Ying (Frontiers in Neuroscience, 2021)
One of the major challenges in treating Alzheimer's disease (AD) is its early diagnosis. Increasing data from clinical and animal research indicate that the retina may facilitate an early diagnosis of AD. However, a previous study on the 5xFAD (a fast AD model), showing retinal changes before those in the brain, has been questioned because of the involvement of the retinal degeneration allele Pde6brd1. Here, we tested in parallel, at 4 and 6 months of age, both the retinal and the brain structure and function in a 5xFAD mouse line that carries no mutation of rd1. In the three tested regions of the 5xFAD brain (hippocampus, visual cortex, and olfactory bulb), the Aβ plaques were more numerous than in wild-type (WT) littermates already at 4 months, but deterioration in the cognitive behavioral test and long-term potentiation (LTP) lagged behind, showing significant deterioration only at 6 months. Similarly in the retina, structural changes preceded functional decay. At 4 months, the retina was generally normal except for a thicker outer nuclear layer in the middle region than WT. At 6 months, the visual behavior (as seen by an optomotor test) was clearly impaired. While the full-field and pattern electroretinogram (ERG) responses were relatively normal, the light responses of the retinal ganglion cells (measured with multielectrode-array recording) were decreased. Structurally, the retina became abnormally thick with few more Aβ plaques and activated glia cells. In conclusion, the timeline of the degenerative processes in the retina and the brain is similar, supporting the use of non-invasive methods to test the retinal structure and function to reflect changes in the brain for early AD diagnosis.